Theoretical understanding of water splitting by analyzing nanocatalyst photoabsorption spectra - Gollapalli Prince; Caspary Toroker Maytal (Nanophotonics)
Photons can be used to either monitor or induce catalysis by acting as photoexcited holes or quasi particles, which aid in water splitting reaction leading to a major step towards sustainable energy. However, the mechanism of catalysis using nanocatalysts under photo-illumination is not fully understood because of the complexity involved in three major steps during the oxygen evolution reaction: photoabsorption on nanocatalyst, hole transport to the surface, and the reaction kinetic barriers at the surface. In a photoelectrochemical cell used for water splitting, the surface states of optically and chemically dominant species affect the catalysts’ performance. For instance, the signature of the dominant absorption peak at 580 nm in the observed spectra of Fe2O3 photoanode can shed light on the oxygen evolution reaction mechanism since each reaction intermediate affects the absorption spectrum, and the absorption coefficient in turn affects the photocurrent. In the recent decade, a combination of different theoretical methods starting from density functional theory up to Bethe–Salpeter equation accounting for excitonic effects helped to establish that the *O intermediate is the rate limiting step in agreement with experimental data. Therefore, this perspective focuses on the complexity and variety of fundamental phenomena involved in water splitting mechanism and various theoretical methods applied to address these and also suggests how the predictive capability of these methods can be used to understand mechanisms beyond water splitting, such as CO2 reduction.